Youth Entrepreneurial Spirit In Family Business - Satria Lintang Rachmadana Lintang Rachmadana (Journal of Business and Management Review, 2021)
As youths who came into business family inheritance, living in an industrial center, naturally, they are indispensable to continue the family business. In conjunction with that, the sustainability of the industrial center also depends on their willingness to be an entrepreneur or not. The methodological approach taken in this study is a qualitative method. The data for this study was collected using semi-structured in-depth interviews. To begin the process, data is collected through editing and classification, then analyzed and interpreted. The research subject in this study is youth whose own family business at the Sanan Tempe industrial center. The data analysis in this study is using Phenomenological Analysis. The data analysis process is divided into 4 stages starting from data managing, reading, describing, presenting. This research found that the entrepreneurial spirit of the youth in the Sanan Tempe industrial center has been formed since an early age. It came naturally from the experience and opportunity to be part of the family business which shaped their psychology and behavior. Another finding on this research is that a high level of education does not necessarily become a barrier for them to run their family business, choosing a profession as entrepreneurs like what their parents did.r them to run their family business, choosing a profession as entrepreneurs like what their parents did.